PENERAPAN MEDIA ASSEMBLR EDU BERBASIS AUGMENTED REALITY (AR) GUNA MENINGKATKAN HASIL BELAJAR SISWA PADA MATERI PEMBELAHAN SEL - Wahyuni, Elfinta; Maulida, Maulida; Hamama, Syarifah Farissi; Samsuar, Samsuar; Zamzami, Zamzami (Center for Research and Community Service (LPPM) University of Abulyatama, 2024)
The purpose of this study is to find out whether the application of Assemblr Edu based biology learning media with Augmented Reality (AR) design can affect student learning outcomes on cell division material. This research was conducted using Quasi Experimental research methods with a quantitative approach. The type of research design used to measure student learning outcomes in this study is Pretest-Posttest Control Group Design. Learning outcome data were analyzed using the Normalized Gain (N-Gain) formula, while the hypothesis was tested using the T-Test formula in the form of Independent Sample T-Test. The population used in this study was all class XII MIA students, consisting of 3 classes. The sample was selected through the Purposive Sampling technique so that 2 classes were obtained, namely class XII-MIA 2 as an experimental class (32 students) and XII-MIA 3 as a control class (33 students). The data collection technique used is a formative test with instruments in the form of Pre-test questions and Post-test multiple-choice forms with as many as 25 items, each item is provided with five alternative answers. Based on the results of the study concluded that the application of Assemblr Edu based biology learning media with Augmented Reality (AR) design can affect the improvement of student learning outcomes in the eyes of cell division material, in the low and ineffective category, so this method is not appropriate to be applied in class XII MIA SMA Negeri 1 Baitussalam T.A 2023/2024